Analisis Penilaian Pengelolaan Lingkungan Menggunakan ISPO, Proper dan Industri Hijau Pada Pabrik Kelapa Sawit PT.X - Muhammad Fadly Rezky Ramadhan; Sillak Hasiany; Prasetio, Bambang (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
As the palm oil industry grows, it will have a negative impact on the environment. To maintain global markets and competitiveness, the government must support the national palm oil industry using sustainable principles. This requires an understanding of the 3 P's (people, planet, profit). To meet the sustainability requirements, the Indonesian government has issued several environmental programs: the Indonesian Sustainable Palm Oil (ISPO), Performance Rating Program and Green Industry. Existing environmental programs have their own strengths and weaknesses, including regulations, principles and stakeholders. A harmonization method is needed to integrate the principles of each program. This study uses the Integrated Management System (IMAS) method to refine their advantages and disadvantages. Existing programs can be integrated if they are related (parallelism) and the principles are aligned. The evaluation shows that the performance level of the ISPO, PROPER and GI programs is well influenced by key factors in the form of top management support, company competitiveness and company vision and mission.